IMPLEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM PENANAMAN NILAI SOSIAL PADA SISWA KELAS SEMBILAN DI SMPIT AS-SALAM MALANG - Diki Mochammad Yusuf; Ika Ratih Sulistiani; Adi Sudrajat (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
The first dream in islamic learning is to produce good people, in achieving this achievement or dream it takes the latest stages and methods so that these goals can be achieved satisfactorily as expected. Therefore, the research conducted by the researcher aims to explain the aplication of upgrading, inculcation of social values, as well as the supporting and inhibiting factors of the implementation of PAI learning in inculcating social values in ninth grade students at SMPIT As-Salam Malang. The method used in this research is qualitative research with the type of case study research. The results of this study indicate that the implementation of PAI learning in inculcating social values in ninth grade students at SMPIT As-Salam Malang, namely planning in the form of syllabus, socialization, lesson plans, implementation of Islamic Religious Education learning in the implementation of inculcating social values in ninth grade students at SMPIT As-Salam Malang consists of two ways, namely intracurricular and extracurricular, evaluation through valid judgment, consideration Â of reference benchmarks, learning produckt notification.